Audiovisual Multisensory Integration and Evoked Potentials in Young Adults With and Without Attention-Deficit/Hyperactivity Disorder - McCracken, Heather S.; Murphy, Bernadette A.; Glazebrook, Cheryl M.; Burkitt, James J.; Karellas, Antonia M.; Yielder, Paul C. (Frontiers in Human Neuroscience, 2019)
The purpose of this study was to assess how young adults with attention-deficit/hyperactivity disorder (ADHD) process audiovisual (AV) multisensory stimuli using behavioral and neurological measures. Adults with a clinical diagnosis of ADHD (n = 10) and neurotypical controls (n = 11) completed a simple response time task, consisting of auditory, visual, and AV multisensory conditions. Continuous 64-electrode electroencephalography (EEG) was collected to assess neurological responses to each condition. The AV multisensory condition resulted in the shortest response times for both populations. Analysis using the race model (Miller, 1982) demonstrated that those with ADHD had violation of the race model earlier in the response, which may be a marker for impulsivity. EEG analysis revealed that both groups had early multisensory integration (MSI) occur following multisensory stimulus onset. There were also significant group differences in event-related potentials (ERPs) in frontal, parietal, and occipital brain regions, which are regions reported to be altered in those with ADHD. This study presents results examining multisensory processing in the population of adults with ADHD, and can be used as a foundation for future ADHD research using developmental research designs as well as the development of novel technological supports.